2016
DOI: 10.1038/srep20623
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation to Ionization of Argon Under Conditions Close to Typical Sonoluminescence Experiments

Abstract: Mott effect, featured by a sharp increase of ionization, is one of the unique properties of partially ionized plasmas, and thus of great interest to astrophysics and inertial confinement fusion. Recent experiments of single bubble sonoluminescence (SBSL) revealed that strong ionization took place at a density two orders lower than usual theoretical expectation. We show from the perspective of electronic structures that the strong ionization is unlikely the result of Mott effect in a pure argon plasma. Instead,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…III, describing electron dynamics in Ni after an initial excitation, the possibility to include laser-excited electron relaxation in TDDFT through the time-dependent modification of fractional occupation numbers f 0 i in the Hamiltonian should be explored. Additionally, the thermalization dynamics in the absence of the laser field can be obtained artificially by introducing strong ionic motion to the system and thus solving molecular dynamics equations together with Kohn-Sham equations [40].…”
Section: Discussion On Thermalization Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…III, describing electron dynamics in Ni after an initial excitation, the possibility to include laser-excited electron relaxation in TDDFT through the time-dependent modification of fractional occupation numbers f 0 i in the Hamiltonian should be explored. Additionally, the thermalization dynamics in the absence of the laser field can be obtained artificially by introducing strong ionic motion to the system and thus solving molecular dynamics equations together with Kohn-Sham equations [40].…”
Section: Discussion On Thermalization Dynamicsmentioning
confidence: 99%
“…Recently it was shown however that TDDFT could indirectly provide a mechanism for the electrons to thermally equilibrate with each other [36]. Moreover the motion of the atoms produce a large number of small electronic transitions affecting the evolution of the electron energy distribution function similar to a thermalization process [34,[37][38][39][40]. For the same reason the external electric potential of a laser pulse contributes to the thermalization of electrons through the photon-electron-ion collisional process and thus TDDFT can reasonably capture the thermalization process during the laser pulse.…”
Section: Introductionmentioning
confidence: 99%
“…However, preceding attempts to do this on the level of the time-dependent density functional theory (TD-DFT) [30][31][32] have shown that this approach is extremely computationally costly. Practically, it is only capable to include tens of atoms in the calculation, which is far less than the required number of atoms to describe the propagation of shock waves.…”
Section: Inertial Confinement Fusion (Icf)mentioning
confidence: 99%
“…We performed ab initio calculations for dense carbon and aluminum with the Abinit code [37][38][39][40][41][42]. For both materials, we performed static DFT calculation using perfect lattices (T = 0 eV) and DFT-MD simulations at a finite temperature (T = 12.5 eV).…”
Section: Ab Initio Simulationsmentioning
confidence: 99%